Möjlighetsstudie av en sond stor som en burk - Christoforidis Johansson, Kevin; Dalevi, Alice; Gustavsson, William; Niens, Patrik (My University, 2024)
This project was based on the American competition CanSat, where every team was tasked with creating a can-sized satellite to launch with a rocket. The task in this specific case was to study the feasibility of developing a satellite based on the dimensions of an American 355ml can, without the actual rocket launch. Using ”trial and error” as the primary approach for mechanical design was established early on and complemented by the integration of Arduino for electrical systems and sensors. Basic theories in fluid mechanics and mechatronics were also utilized. Every subsystem was tested individually, to ensure they worked as intended. The final prototype did reach a mostly satisfactory result with some subsystems not fulfilling the requirements set prior to the tests. Other subsystems were left out, due to time constraints. Overall, the project showed that it is feasible to create a can-sized satellite. However, more time and resources would be needed to reach a product that complies entirely with the requirement list and can partake in the actual competition.
Keywords: CanSat; satellite; feasibility; American; rocket; fluid mechanics; Arduino